Estimation of Above Ground Biomass and Carbon Stock using UAV images - Upadhyaya, Sandesh; Gyawali, Prabin; Sapkota, Sambhav; Neupane, Nishan; Neupane, Manoj (Journal on Geoinformatics, Nepal, 2023)
Forests have a vital role in maintaining global climate stability by removing greenhouse gases like carbon dioxide from environment. Estimation of carbon stock is crucial in quantifying the amount of carbon that is present in the forest. The estimation of forest biomass and carbon stock through field measurements is a challenging and timeconsuming task. Here in this scenario, our study aims to estimate carbon stock in a forest area using the hybrid technique i.e., aerial survey and ground survey. We used low-altitude remote sensing data acquired by UAV to estimate biomass and carbon stock in an efficient way compared to the traditional techniques. We developed an orthomosaic from the collected aerial imageries and manually delineated tree crowns to obtain crown projection area (CPA) for the entire study area using GIS tools. Our study area contained a mixed species with Pinus Wallichiana to be the dominant species while other species are negligible. Using field-measured tree height and diameter at breast height (DBH) as input, we estimated above-ground biomass (AGB) with an allometric equation and then used a factor value to estimate carbon stock or aboveground carbon (AGC) for six sample plots. Next, we developed a relationship between CPA and carbon stock and validated it by comparing the carbon stock values obtained from the allometric equation for the remaining four sample plots. Among the various developed model, 4th order Polynomial model was chosen due to its highest coefficient of correlation. After the model validation was done the AGC of whole study area was obtained by using the CPA delineated manually from the orthomosaic image. The total AGC and AGB obtained for our study area which was about 7 hectare was 210.7480 tons and 448.4 tons respectively.